2008
DOI: 10.1016/j.freeradbiomed.2008.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin-induced prostate cancer cell death is initiated by reactive oxygen species and p53 activation

Abstract: Apigenin, a plant flavone, potentially activates wild-type p53 and induces apoptosis in cancer cells. We conducted detailed studies to understand its mechanism of action. Exposure of human prostate cancer 22Rv1 cells, harboring wild-type p53, to growth-suppressive concentrations (10-80 μM) of apigenin resulted in the stabilization of p53 by phosphorylation on critical serine sites, p14 ARFmediated downregulation of MDM2 protein, inhibition of NF-κB/p65 transcriptional activity, and induction of p21/WAF-1 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 48 publications
(84 reference statements)
8
87
0
1
Order By: Relevance
“…Interestingly, neither melatonin nor silibinin are able to induce cell death which makes a difference in the outcome triggered by other antioxidants. 42,43 On the contrary, both antioxidants redirect cells toward a transdifferentiation process that matches a NE-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, neither melatonin nor silibinin are able to induce cell death which makes a difference in the outcome triggered by other antioxidants. 42,43 On the contrary, both antioxidants redirect cells toward a transdifferentiation process that matches a NE-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism by which DIM causes DNA damage was not clear. Previous studies have indicated the involvement of ROS in causing DNA damage in pancreatic and prostate cancer cells (Shukla and Gupta, 2008;). In agreement with these studies, our present results also show the generation of ROS by DIM and the involvement of ROS in causing DNA damage, leading to G 2 /M arrest.…”
Section: Discussionmentioning
confidence: 99%
“…This is typical for prostate cells [17][18][19][20][21][22][23][24][25], pancreatic cancer cells [26][27][28][29][30][31][32][33], melanoma cells [34][35], breast cancer cells [36][37][38][39], and other cancer cells [40][41][42][43][44][45][46][47][48][49][50]. It is important that the elevated ROS formation in cancer cells can have both surviving and hindering effects.…”
Section: Cancermentioning
confidence: 99%